The Influence of Product Availability, Price, and Product Quality on Consumer Repurchase Intention - Ferdyansyah, Mico; Maidalena (Amkop Management Accounting Review (AMAR), 2025)
Repurchase intention is a consumer's interest in making a repeat purchase based on previous purchasing experiences. High repurchase intention reflects a high level of consumer satisfaction when deciding to adopt a product. This study aims to examine the influence of product availability, price, and product quality on consumer repurchase intention. This study uses a quantitative approach. The sampling method was carried out using an accidental sampling technique. The number of respondents in this study was 70 people, because this number has exceeded the minimum limit according to Roscoe's opinion. The data collection technique was carried out through a questionnaire with statements related to the research variables and in accordance with the research title, and was supplemented by observation and interviews. The data analysis technique used in this study was descriptive quantitative with a multiple linear regression analysis model. Data analysis was carried out using SPSS version 20 software. The results of the study showed that product availability and product quality partially influenced consumer repurchase intention, while price did not influence repurchase intention. Meanwhile, simultaneously, product availability, price, and product quality jointly influenced consumer repurchase intention.